The impact of individual differences on cross-language activation of meaning by phonology. Issue 2 (10th March 2020) - Friesen, Deanna C.; Whitford, Veronica; Titone, Debra; Jared, Debra
Abstract : We investigated how individual differences in language proficiency and executive control impact cross-language meaning activation through phonology. Ninety-six university students read English sentences that contained French target words. Target words were high- and low-frequency French interlingual homophones (i.e., words that share pronunciation, but not meaning across langauges; mot means 'word' in French and sounds like 'mow' in English) and matched French control words (e.g., mois – 'month' in French). Readers could use the homophones' shared phonology to activate their English meanings and, ultimately, make sense of the sentence (e.g., Tony was too lazy to mot/mois the grass on Sunday ). Shorter reading times were observed on interlingual homophones than control words, suggesting that phonological representations in one language activate cross-language semantic representations. Importantly, the magnitude of the effect was modulated by word frequency, and several participant-level characteristics, including French proficiency, English word knowledge, and executive control ability.